Revision of the genus Theopea Baly (Coleoptera: Chrysomelidae: Galerucinae) in Sundaland and the Philippines: Redefinition of the genus - Lee, Chi-Feng; Bezdĕk, Jan (Zootaxa, 2019)
The genus Theopea Baly, 1864 is redefined. Seventeen species from Sundaland and the Philippines are recognized and classified into four species groups (including seven new species): T. impressa (Fabricius, 1801), T. longicollis (Jacoby, 1896), T. louwerensi Jolivet, 1951, T. lunduensis Mohamedsaid, 1998, T. chungi sp. nov. in the T. impressa group; T. flavipalpis Laboissère, 1940, T. guoi sp. nov., T. lui sp. nov., T. sabahensis sp. nov. in the T. flavipalpis group; T. elegantula Baly, 1864, T. pulchella Baly, 1864, T. fairmairei Duvivier, 1885, T. kedenburgi Weise, 1922, T. houjayi sp. nov., T. tsoui sp. nov., T. yuae sp. nov. in the T. pulchella group; and T. costata (Allard, 1889) in the T. costata group. The following new synonyms are established: Theopea pulchella Baly, 1864 = T. nigricollis Jacoby, 1892 syn. nov.; Theopea impressa (Fabricius, 1801) = T. impressa flavicornis Laboissère, 1940 syn. nov. and T. impressa malaccana Laboissère, 1940 syn. nov.; T. lunduensis Mohamedsaid, 1998 = T. sepilokensis Mohamedsaid, 2000 syn. nov. Lectotypes are designated for Crioceris impressa Fabricius, 1801, Ozomena longicollis Jacoby, 1896, Theopea elegantula Baly, 1864, T. fairmairei Duvivier, 1885, T. nigricollis Jacoby, 1892, and T. pulchella Baly, 1864. Theopea obliterata Jacoby, 1884, T. variabilis (Jacoby, 1887), T. incostata (Allard, 1889), T. clypeata Jacoby, 1896, T. modiglianii Jacoby, 1896, T. dohrni (Jacoby, 1899), T. viridipennis (Jacoby, 1899), and T. weberi (Weise, 1913) are removed from Theopea and regarded as species incertae sedis.